The domestic abroad : diasporas in international relations - Varadarajan, Latha (New York ; Oxford : Oxford University Press, 2010)
In this text, the author proposes a re-consideration of both the meaning of transnationalism and the nature of national and state identity in global politics. In order to do this, Varadarajan draws from two literatures that are rarely brought into conversation with IR scholarship: postcolonial theory and historical-materialism.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Transnationalism -- Social aspects -- Developing countries; Dual nationality -- Developing countries; Developing countries -- Emigration and immigration; Developing countries -- Foreign relations